Compliance and Resistance Within Neoliberal Academia Biographical Stories, Collective Voices - Gair, Susan (Springer Nature, 2021)
This open access book reflects on academic life under a neoliberal regime. Through collaborative autoethnographies, the authors share stories about the everyday experiences, dilemmas and conflicts of three academics: the struggle for promotion, teaching's challenges, the race to publish, confronting bureaucracy and institutional politics, as well as the resulting emotional stress. These stories reveal the impact of neoliberal culture on ideological, economic, social, collegial, and emotional integrity which are integral to academics' lives today. But along with the challenges, the authors present their vision of hope, and transformation through academic solidarity - and for the silenced voices to be heard, inside academia and beyond it. This is an open access book.